Ein russischer Atlas des Wärmehaushalts der Erdoberfläche - Flohn, Hermann (ERDKUNDE, 1958)
This is a review article of the Atlas of the Temperature Regime, edited by M. I. Budyko (Leningrad), and the accompanying monograph. The most important numerical values of the temperature and insolation regime within the latitudes 60°N-60°S, and of the continents and oceans (including the water cycle) are appended in two tables.